The happy camper ebook - Carlson, Melody (2020)
When Dillon Michaels returns home after a breakup, her grandfather gifts her a vintage camp trailer that needs restoration. Intrigued by the work, and the charming hardware store owner, she's hopeful for a fresh chance at love—until a surprise visit from her ex-boyfriend turns everything upside down.